Penerapan Terapi Kognitif dan Senam Lansia dalam Upaya Menjaga Kesehatan Fisik dan Mental Lansia di Masa Pandemi Covid 19 - Artama, Syaputra; Wawomeo, Aris; Tokan, Pius Kopong (LPPM Universitas Flores, 2022)
The COVID-19 outbreak, which in recent years has become a pandemic in almost all countries in the world, has had a negative impact on the physical and psychological health of individuals and communities. One of the age groups that is a concern during this pandemic is the elderly. During the pandemic, to prevent the elderly from feeling lonely, anxious, stressed which can affect the health of the elderly such as a decrease in the body's immunity, decreased cognitive function, a program of elderly activities is needed, including cognitive therapy and elderly gymnastics. The health conditions and psychological conditions faced by the elderly during the pandemic as a whole can have an impact on health, especially on the body's immunity and the quality of life of the elderly. The purpose of this activity is so that the elderly can take an active role in cognitive therapy and gymnastics activities for the elderly and understand and apply the importance of maintaining health during a pandemic. This strengthening is a preventive and rehabilitative effort in improving the health and quality of life of the elderly. The form of activity program carried out by the method of carrying out socialization, implementing cognitive therapy in the elderly, seeing the results of evaluation of changes after therapy is carried out, carrying out elderly gymnastics activities in Gheo Ghoma Village, Ende Regency. The results of this activity can be seen from the participation of the elderly in carrying out cognitive therapy and gymnastics for the elderly. There are changes in the cognitive improvement of the elderly after therapy and an increase in public insight and understanding of the importance of maintaining the health of the elderly during the Covid-19 pandemic. Cognitive therapy and elderly gymnastics programs are simple things that need to be done regularly and consistently, in order to build community awareness in maintaining the health of the elderly and improving the quality of life of the elderly, especially during the current pandemic